A rare case of voluminous brain abscess due to Actinomyces meyeri and Aggregatibacter aphrophilus: is there any evidence for a prolonged antibiotic oral relay?. Issue 8 (August 2021) - Altdorfer, Antoine; De Cassem, Jafar; Gavage, Pierre; Mathonet, Pierre-Yves; Guzmán-Suárez, Silvia; Moerman, Filip
Abstract: We present the case of a patient with a voluminous cerebral abscess caused by Aggregatibacter aphrophilus and Actinomyces meyeri occurring a week post dental scaling. Both these bacteria are rarely involved in brain abscesses, and so far, cases of cerebral actinomyces have mostly been treated surgically and with intravenous (IV) antibiotics for 3–4 months, then put on oral antibiotic therapy with penicillin or amoxicillin for a further 3–12 months. Our patient underwent drainage through craniotomy and was subsequently put on intravenous ceftriaxone for 3 months accompanied by brain imaging control at the end of this period which showed complete regression of the abscess. Following parenteral treatment, no oral antibiotics were given since pharmacokinetic properties do not allow to attain high tissue concentration in the brain. This treatment gave excellent results.